PENINGKATAN HASIL BELAJAR MENGGUNAKAN TIPE NUMBERED HEAD TOGETHER DALAM PEMBELAJARAN TEMATIK DI KELAS IV - Riennova, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to describe the improvement of students’ achievement in thematic learning by using numbered head together type to year 4B students at SD Negeri 17 Pontianak Kota. The research used descriptive method. The research design used was classroom action research. The subject of the research was a teacher and thirty students of year 4B. Tools of data collecting were instrument of teacher’s observasion sheets (IPKG 1and IPKG 2) and written test to measure students’ achievement. Tools of data analysis used was average score pattern. The results of this research showed that the average score of teacher’s ability in planning thematic learning by using numbered head together type at cycle 1 was 3,65 and improved to 3,89 at cycle 2. The average score of teacher’s ability in implementing thematic learning by using numbered head together at cycle 1 was 3,47 and improved to 3,87 at cycle 2. The average score of students’ achievement at cycle 1 was 88,67 and at cycle 2 improved to 92,67 excedeed the passing grade of 70,00. Based on data analysis, showed that the use of numbered head together type could improve teacher’s ability in planning and implementing thematic learning to improve students’ achievement.   Keywords:Thematics Learning, Numbered Head Together Type, Achievement